Socialization of Simple Books to Improvement The Quality of School Management - Neneng Sri Suprihatin (EQUATOR SINAR AKADEMIA, 2022)
Community Service Activities are carried out in Lontar Baru Village, Serang District, with the target of teaching staff and finance in the service partners' environment. This activity aims to provide counseling or socialization in order to increase understanding and knowledge of financial reporting, as well as knowledge of financial accounting in order to improve the quality of school management. This community service activity method uses lecture and practice methods. The lecture method is used to deliver material and ask questions. Community service is also carried out with direct practice by assisting in recording, bookkeeping, and making simple financial reports. The output of this activity is simple school bookkeeping and in accordance with applicable financial accounting standards which produces financial reports for PAUD A-Ba-Ta Schools. For this reason, partner management is expected to be able to record cash flows in and out, as well as record other operational activities easily and the results can be used properly.